KUAT TEKAN BAMBU LAMINASI DAN APLIKASINYA PADA RUMAH TRADISIONAL BALI (BALE DAJE/BANDUNG) - Eratodi, I.G.L. Bagus; Morisco, Morisco; Prayitno, T.A. (Civil Engineering Forum Teknik Sipil, 2008)
Building material technological development recently is very fast, and in every technological innovation creation, it’s inspired by some of the main purpose, such as: cost efficiency, material use optimization, conservation and development of natural material, smart building material technology and ecologically friendly. Lamination bamboo technology is a product that can act as substitution material of wood that can be customized with the need. In the effort to support the innovation of lamination bamboo as a wood substitution in Balinese traditional building, the characteristic mechanics of lamination bamboo as column in supporting axial loading should be known. Lamination bamboo for the experiemnt was made in the form of column with two kind of longitudinal section dimension, size 20x20 mm with slenderness value (λ) of 50, 75, 100, 125, and 150, and size 120x120 mm with the length of 2400 mm (as the dimension in Balinese traditional building). The bamboo used were petung bamboo made of blade about 5x20 mm attached to glue of Urea Formaldehyde (UF) and pressed with a pressure of 2,0 MPa. The research stage was physical property test and the mechanic of petung bamboo material, and continued with a process of making the lamination bamboo column and carving. Pressure axial loading for testing of column the lamination bamboo used hinge placement bamboo until maximum loading, big deformation and not until collapse. The technological innovation of lamination bamboo was able to increased the pressure strength of blade until 36,02% compared to the bamboo material used. The role of glue and pressing given a substantial contribution on pressure strength of lamination bamboo, so besides having a capability to be made with dimension and form us want, lamination bamboo also had high pressure strength. Lamination bamboo pressure strength of petung bamboo in variety of slenderness had pressure strength less with the higher slenderness. The pressure voltage in the smallest slenderness, λ=50 is 60,093 MPa until the blade with the highest slenderness, λ=150 is 12,946 MPa while for the plain and carved structural model they were 25,578 MPa and 23,529 Mpa respectively. The formula of proposal in column pressure strength modeling of lamination bamboo material for for λ< λb , σtk = σd [1-0.4 λr2] and λ> λb, σtk = (π2E)/λ r2. The treatment of carving in structural lamination bamboo column weakens the support to average axial load of 41,15% and the decrease of average pressure voltage of 8,009%.